(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The genus Convolvulaceae (Linn.) refers to Silva Manso (OT). The study covers phytochemical and pharmaceutical profile literature from the OT herbs. A thorough literary analysis was carried out using all the available information on OT phytochemistry and pharmacology. The plant was found to be a powerful source of bioactive compounds, such as α- and β-turpethein, turpethinic acids (A, B, C, D and E), coumarins, cycloartenols, lanota-5-enes,24-methylen-to-lanosterol, alpha and rhamnose, β-sitosterol, lupeol, scopoletin, Betolin, acrylamide, stigma‐5,22dien‐3‐o‐β‐D‐glucoide (H‐1). Four new dammaranes, operculinosides A–D (1–4), which had special hepatoprotective activity are extracted from the aerial sections of OT. It has been documented that all the compounds have pharmacological properties such as antibacterial, analgesic, anti-arthritis, anti-inflammatory, anti-inflammatory and biopsy.